2001
DOI: 10.1103/physrevlett.86.4930
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Phonon Bottleneck in Quantum Dot Electronic Relaxation

Abstract: Time-resolved differential transmission measurements of self-assembled In0.4Ga0.6As quantum dots clearly indicate a phonon bottleneck between the n = 2 and n = 1 electronic levels. The key to this observation is the generation of electrons in dots where there are no holes so that electron-hole scattering does not mask the bottleneck. We use a simple carrier capture model consisting of two capture configurations to explain the bottleneck signal and offer arguments to rule out other possible sources of the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
172
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(189 citation statements)
references
References 18 publications
13
172
3
1
Order By: Relevance
“…This relaxation is different if an electron-hole pair is present or just a sole electron (doped dot). As expected from the phonon bottleneck effect, inter-shell relaxation in (In,Ga)As/GaAs dots has been observed to be slow by Urayama and coworkers 23 (relaxation time of ∼ 750 ps) as well as Heitz and co-workers 27 (7.7 ns). In contrast, time-resolved optical measurements have clearly demonstrated that this inter-shell decay is a fast process whether a hole is present or not.…”
Section: Characteristic Dynamical Processes Of Excited Electrons mentioning
confidence: 70%
See 1 more Smart Citation
“…This relaxation is different if an electron-hole pair is present or just a sole electron (doped dot). As expected from the phonon bottleneck effect, inter-shell relaxation in (In,Ga)As/GaAs dots has been observed to be slow by Urayama and coworkers 23 (relaxation time of ∼ 750 ps) as well as Heitz and co-workers 27 (7.7 ns). In contrast, time-resolved optical measurements have clearly demonstrated that this inter-shell decay is a fast process whether a hole is present or not.…”
Section: Characteristic Dynamical Processes Of Excited Electrons mentioning
confidence: 70%
“…Such a hole relaxation has been found to occur within sub-ps times. 16,23 Moreover, Quochi and co-workers showed that the hole relaxation time depends strongly on temperature: 20 ps at 60 K and 0.8 ps at 300 K (Ref. 24).…”
Section: Characteristic Dynamical Processes Of Excited Electrons mentioning
confidence: 99%
“…The ultrafast response and high detection efficiency of the integrated SSPDs enables us to probe the PL dynamics at low excitation levels. In such a scenario carrier capture and energy relaxation is inefficient due to the discrete electronic arXiv:1407.0593v3 [cond-mat.mes-hall] 15 Aug 2014 structure of the dots and the absence of Coulomb mediated scattering involving carriers occupying energetically higher discrete states 8 . In particular, an excitation power dependent change in inter-sublevel relaxation times is observed for a single, spatially isolated QD.…”
mentioning
confidence: 99%
“…Slow phonon thermalisation [6] has been observed in some nano-structured materials and it might perhaps appear in some large band gap bulk materials like InN with large phononic band * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%